Improving Educational Personnel Quality Through Empowerment and Delegation to Enhance Work Motivation - Yasril Yasril; Syaiful Marwan (Ta'dib, 2024)
Job enrichment and delegation of authority are widely recognized as effective strategies to enhance the performance of educational staff and increase organizational productivity. However, at the Tanah Datar Regency Education and Culture Office, these strategies are not yet being implemented as expected. This study aims to optimize worker education by examining the contributions of job enrichment and delegation of authority to work motivation. The study tests three hypotheses: (1) job enrichment contributes to the work motivation of educational staff; (2) delegation of authority contributes to the work motivation of educational staff; and (3) job enrichment and delegation of authority together contribute to the work motivation of educational staff. The research involved 140 educational staff members, with a random sample of 57 selected using a stratified proportional random sampling technique based on educational level, class, and length of service. Data were collected using a validated and reliable Likert scale questionnaire. The findings reveal that job enrichment contributes 16% to work motivation, delegation of authority contributes 28.09%, and the combined contribution of both factors is 42%. The current levels of job enrichment and delegation of authority at the Tanah Datar Education and Culture Office are considered sufficient, while the work motivation of educational staff is rated as good. The study underscores the importance of enhancing job enrichment and delegation of authority to further boost staff motivation and achieve better organizational outcomes.